2014
DOI: 10.1038/srep04208
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidium parvum IId family: clonal population and dispersal from Western Asia to other geographical regions

Abstract: In this study, 111 Cryptosporidium parvum IId isolates from several species of animals in China, Sweden, and Egypt were subtyped by multilocus sequence typing (MLST). One to eleven subtypes were detected at each of the 12 microsatellite, minisatellite, and single nucleotide polymorphism (SNP) loci, forming 25 MLST subtypes. Host-adaptation and significant geographical segregation were both observed in the MLST subtypes. A clonal population structure was seen in C. parvum IId isolates from China and Sweden. Thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
68
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 43 publications
10
68
1
Order By: Relevance
“…However, this subtype is not common in dairy cattle in Australia (Ng et al 2012;Abeywardena et al 2013b). Previous analysis has indicated that C. parvum IId subtypes were probably dispersed from Western Asia to other geographical regions (Wang et al 2014). As water buffalo in Australia came from Asia (Letts 1964), it is likely that the IId subtype family was introduced into Australia with the introduction of buffalo.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, this subtype is not common in dairy cattle in Australia (Ng et al 2012;Abeywardena et al 2013b). Previous analysis has indicated that C. parvum IId subtypes were probably dispersed from Western Asia to other geographical regions (Wang et al 2014). As water buffalo in Australia came from Asia (Letts 1964), it is likely that the IId subtype family was introduced into Australia with the introduction of buffalo.…”
Section: Discussionmentioning
confidence: 99%
“…In China, IId is the predominant C. parvum subtype (Wang et al 2014), and both of these IId subtypes are commonly found in bovine animals in China including yaks (Wang et al 2014;Qi et al 2015). However, this subtype is not common in dairy cattle in Australia (Ng et al 2012;Abeywardena et al 2013b).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations